2018
DOI: 10.1039/c8dt00601f
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited-film electrodes derived from a precursor dinitrosyl iron complex for electrocatalytic water splitting

Abstract: In artificial photosynthesis, water splitting plays an important role for the conversion and storage of renewable energy sources. Here, we report a study on the electrocatalytic properties of the electrodeposited-film electrodes derived from irreversible electro-reduction/-oxidation of a molecular dinitrosyl iron complex (DNIC) {Fe(NO)2}9 [(Me6tren)Fe(NO)2]+ (Me6tren = tris[2-(dimethylamino)ethyl]amine) for the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) in alkaline solution, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Complexes 99 , 142 and 153 were incorporated into heterogeneous electrodes to constitute remarkable HER catalysts, capable of reducing protons from water. Liaw and coworkers used the {Fe­(NO) 2 } 9 /{Fe­(NO) 2 } 10 redox couple in DNICs to design complexes for a solid-state hydrogen evolution cathode. ,, The low-cost PMDTA-bound DNIC 142 , deposited on an electrode, exhibits a low onset potential of -717 mV versus SHE in a neutral 1.0M KCl solution to generate H 2(g) from water . The catalytic activity of DNICs can be further tuned by ligand design.…”
Section: Dinitrosyl Iron Complexes (Dnics)mentioning
confidence: 99%
“…Complexes 99 , 142 and 153 were incorporated into heterogeneous electrodes to constitute remarkable HER catalysts, capable of reducing protons from water. Liaw and coworkers used the {Fe­(NO) 2 } 9 /{Fe­(NO) 2 } 10 redox couple in DNICs to design complexes for a solid-state hydrogen evolution cathode. ,, The low-cost PMDTA-bound DNIC 142 , deposited on an electrode, exhibits a low onset potential of -717 mV versus SHE in a neutral 1.0M KCl solution to generate H 2(g) from water . The catalytic activity of DNICs can be further tuned by ligand design.…”
Section: Dinitrosyl Iron Complexes (Dnics)mentioning
confidence: 99%
“…Regarding the biological discovery of the natural [Fe­(NO) 2 ] motif as a possible form for the storage and transport of NO, LMW DNIC derived from nitrosylation of the aqueous solution of iron salts, despite the lack of its structural characterization, was adopted to trigger the NO-related function on the activation of soluble guanylate cyclase, , heat-shock protein 70 (HSP70), , nonselective cationic channel, apoptosis, ,, vasodilation, ,,− skin wound healing, , and penile erectile, as well as on the inhibition of Na/K-ATPase, glutathione reductase, glutathione S -transferase, enteroviral rotease A, and platelet aggregation. , To translate this NO-related biological and physiological activity of LMW DNIC into NO-related pharmacology and biomedical application, biomimetic syntheses and crystallographic characterization of mononuclear {Fe­(NO) 2 } 9 /{Fe­(NO) 2 } 10 DNICs, dinuclear {Fe­(NO) 2 } 9 -{Fe­(NO) 2 } 9 /{Fe­(NO) 2 } 9 -{Fe­(NO) 2 } 10 /{Fe­(NO) 2 } 10 -{Fe­(NO) 2 } 10 DNICs, mononuclear {Fe­(NO) 3 } 10 TNICs, and homoleptic {Fe­(NO) 4 } 13 iron complexes build up the chemical library of DNICs (Figure ). ,,,,,, , , ,,, , ,, , ,, ...…”
Section: Evolution Of the Functional Model: Redesign Of Natural Dnics...mentioning
confidence: 99%
“…As reported in the previous study on the implementation of DNICs as homogeneous HER electrocatalysts in aqueous solution, the subsequent deposition of the amount of iron (oxy)hydroxide on graphite electrode during the electrocatalytic HER process demonstrated that DNICs act as a precursor of the heterogeneous HER catalyst . After the extended electrolysis of 1.0 M Na 2 SO 4 aqueous solution with DNICs 1 / 3 – 6 (1 mM) at an applied potential of −1.20 V (vs. SHE) for 1 hr, DNICs 1 / 3 – 6 were reduced to generate catalytically active film on the glassy carbon electrodes that act as the heterogeneous electrodeposited‐film electrodes for HER.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, {Fe(NO) 2 } 10 DNIC [(PMDTA)Fe(NO) 2 ] was employed as a precursor to derive the electrodeposited solid‐state HER catalysts . It is demonstrated that the components of the electrodeposited catalyst are the mixture of the metallic iron and iron oxides . In addition, the surface area of electrodeposited catalyst is larger than that of iron salts‐derived catalyst .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation